1999
DOI: 10.1002/(sici)1098-2396(19990601)32:3<147::aid-syn1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of riluzole: An electrophysiological and histological analysis in an in vitro model of ischemia

Abstract: The protective effects of riluzole against the neuronal damage caused by O2 and glucose deprivation (ischemia) was investigated in rat cortical slices by recording electrophysiologically the cortico-cortical field potential and by evaluating histologically the severity of neuronal death. Five minutes of ischemia determined an irreversible depression of the amplitude of the field potential. In addition, this insult caused a clear enhancement of the number of death cells that were specifically colored with trypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Following 3-5 min incubation with trypan blue, the cells in the culture plates are fixed with 4% buffered formaldehyde and counted under a normal light microscope. In each field, the dead and total number of cells is counted and their ratio provides an estimate of percentage cell death [129]. …”
Section: Introductionmentioning
confidence: 99%
“…Following 3-5 min incubation with trypan blue, the cells in the culture plates are fixed with 4% buffered formaldehyde and counted under a normal light microscope. In each field, the dead and total number of cells is counted and their ratio provides an estimate of percentage cell death [129]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have observed that a more evident protection is obtained perfusing the slices with the strictly-related local anesthetic lidocaine. Several studies have suggested that sodium channel blockers have a neuroprotective role in ischemic brain conditions (Obrenovitch, 1998;Probert et al, 1997;Siniscalchi et al, 1998Siniscalchi et al, , 1999Smith and Meldrum, 1995;Taylor and Meldrum, 1995;Weber and Taylor, 1994;Wiard et al, 1995). It is believed that this protection mainly depends on the inhibition of voltage-sensitive sodium channels (Calabresi et al, 2003a,c;Meldrum, 1996;Siniscalchi et al, 1998Siniscalchi et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an aggravating cellular damage is also produced by the increased energy demand in the absence of fuelling substrates necessary to eliminate the excess of sodium by the Na + /K + pump. As a matter of fact, many blockers of voltage-sensitive sodium channels have demonstrated neuroprotective properties in situations of energy deprivation (Calabresi et al, 1996;Cheung et al, 1992;Crumrine et al, 1997;Siniscalchi et al, 1998Siniscalchi et al, , 1999. For instance, it has been demonstrated that the sodium channel blocker and local anesthetic lidocaine exhibits neuroprotection in animal models of stroke (Butterworth and Hammon, 2002;Evans et al, 1984Evans et al, , 1989Lei et al, 2001Lei et al, , 2002Lei et al, , 2004Mitchell et al, 1999;Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Riluzole is also able to stimulate the large-conductance calcium-activated potassium channels in rat pituitary GH3 cells, to block in vitro the effects of NMDA and kainate in the rat striatum (Keita et al, 1997), and to exert neuroprotective properties in a model of ischemia (Siniscalchi et al, 1999). It has been also demonstrated that glutamatergic transmission pre-and postsynaptically is altered by riluzole (Cheramy et al, 1992;Hubert and Doble, 1989), although radioligand binding studies have not demonstrated that riluzole interacts directly with the glutamate receptors (Benavides et al, 1985;Debono et al, 1993;Koek and Woods, 1988).…”
Section: Discussionmentioning
confidence: 99%